Disposable Bioreactors II - Eibl, Dieter.; Eibl, Dieter.; Eibl, Regine.; Eibl, Regine. (Advances in Biochemical Engineering/Biotechnology,, 2014)
Christian Löffelholz, Stephan C. Kaiser, Matthias Kraume, Regine, Eibl, Dieter Eibl Dynamic Single-Use Bioreactors Used in Modern Liter- and m3- Scale Biotechnological Processes: Engineering Characteristics and Scaling Up  Wolf Klöckner, Sylvia Diederichs, Jochen Büchs, Orbitally Shaken Single-Use Bioreactors Christian van den Bos, Robert Keefe, Carmen Schirmaier, Michael McCaman Therapeutic Human Cells: Manufacture for Cell Therapy/Regenerative Medicine Regine Eibl, Nina Steiger, Sabine Wellnitz, Tiago Vicente, Corinne John, Dieter Eibl Fast Single-Use VLP Vaccine Productions Based on Insect Cells and the Baculovirus Expression Vector System: Influenza as Case Study Thomas Dreher, Bart Walcarius, Ute Husemann, Franziska Klingenberg, Christian Zahnow, Thorsten Adams, Davy de Wilde, Peter Casteels, Gerhard Greller Microbial High Cell Density Fermentations in a Stirred Single-Use Bioreactor Sheena J. Fraser, Christian Endres, Quorus Bioreactor: A New Perfusion-Based Technology for Microbial Cultivation Friederike Hillig, Maciej Pilarek, Stefan Junne, Peter Neubauer Cultivation of Marine Microorganisms in Single-Use Systems Bernhard Diel, Christian Manzke, Thorsten Peuker Flexible Biomanufacturing Processes that Address the Needs of the Future Magali Barbaroux, Susanne Gerighausen, Heiko Hackel An Approach to Quality and Security of Supply for Single-Use Bioreactors Tobias Merseburge, Ina Pahl, Daniel Müller, Markus Tanner A Risk Analysis for Production Processes with Disposable Bioreactors.